2019
DOI: 10.1029/2019jd030586
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unidirectional Vertical Wind Shear on Tropical Cyclone Intensity Change—Lower‐Layer Shear Versus Upper‐Layer Shear

Abstract: In this study, a quadruply nested, nonhydrostatic tropical cyclone (TC) model is used to investigate how the structure and intensity of a mature TC respond differently to imposed lower‐layer and upper‐layer unidirectional environmental vertical wind shears (VWSs). Results show that TC intensity in both cases decrease shortly after the VWS is imposed but with quite different subsequent evolutions. The TC weakens much more rapidly for a relatively long period in the upper‐layer shear than in the lower‐layer shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 61 publications
5
29
0
Order By: Relevance
“…This strongly suggests that the upperlayer VWS is a good indicator of the intensity change of the two interacting strong TCs. Note that the more detrimental effect of the upper-layer VWS on the intensity of a single mature TC has been also found in previous studies (e.g., Xu and Wang 2013;Fu et al 2019).…”
Section: Accepted For Publication Insupporting
confidence: 82%
See 1 more Smart Citation
“…This strongly suggests that the upperlayer VWS is a good indicator of the intensity change of the two interacting strong TCs. Note that the more detrimental effect of the upper-layer VWS on the intensity of a single mature TC has been also found in previous studies (e.g., Xu and Wang 2013;Fu et al 2019).…”
Section: Accepted For Publication Insupporting
confidence: 82%
“…Figure 3 shows the mean potential temperature anomaly in the eye region of the WTC in the four binary experiments. The potential temperature anomaly was calculated as the perturbation relative to the environment, which was the mean potential temperature from the TC surface center to 600-km radius, the same as that in Fu et al (2019). Following Zhang and Chen (2012), we also calculated the central sea level pressure rises induced by the upper-level (between the 9-and 16km heights, ∆ ), lower-level (between the 2-and 6-km heights, ∆ ) and total-level warm core (∆ ) using the hydrostatic equation with the results shown in Fig.…”
Section: Accepted For Publication Inmentioning
confidence: 99%
“…Figure 6 shows the spatial distributions of the averaged VWSs between 200 and 850 hPa in the boreal summers from 2000 to 2018 over the study region. Environmental VWS is defined as the absolute difference of the wind vectors between 200 hPa (upper troposphere) and 850 hPa (lower troposphere) which is more representative of the troposphere‐deep shear experienced in tropical storms (Aiyyer & Thorncroft, 2006; Chen et al, 2006; Fu et al, 2019; Gray, 1968; Heymsfield et al, 2006; Kossin, 2017; Zeng et al, 2008, 2010). The VWS ranges from −13.4 to 8.6 m s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…These opposite findings, which were obtained from model simulation studies, motivated us to investigate the potential connections between dust and the meteorological parameters which affect the formation and development of TCs from an observational viewpoint. Previous studies have revealed that the strong low‐level relative vorticities, mean SSTs higher than 27°C, and VWS from 200 to 850 hPa less than the 10–15 m s −1 are necessary for TC genesis and intensification (Bracken & Bosart, 2000; Fu et al, 2019; Vimont & Kossin, 2007; Webster et al, 2005). VWS is a detrimental factor for the formation of TCs, especially at low latitudes and for small TCs (Aiyyer & Thorncroft, 2006; Bracken & Bosart, 2000; DeMaria, 1996; Fu et al, 2019; Jones, 1995; Kossin, 2017; Murakami et al, 2018; Zeng et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation